ACDC: a simple app for abdominal wall closure data collection - Kothari, Reena; Mukati, Prachir; Sharma, Dhananjaya (International Journal of Research in Medical Sciences, 2018)
Background: With the aims of getting evidence-based guidelines and decision making, well supported by strong, high quality data. We have developed an easy surgeon friendly mobile app which can be customized to the need by just decoding it. Methods: We have use this app to analyze the outcomes of midline rectus sheath closure with different techniques and different sutures in terms of SSI, wound dehiscence, suture knot granuloma, burst abdomen and incisional hernia(IH). All the details regarding patient’s demographic status, surgical technique, suture used and follow up were recorded in the form of EDC (Electronic Data Collection) with the mobile app. Results: Total 595 cases with mean age 48 years underwent midline closure. The most preferred technique was continuous running technique with polypropylene suture (54.1%) followed by herringbone technique with polypropylene suture (27.7%), continuous running technique with polyglactin suture (18. 2%).The incidence of IH was 4.05% with continuous running technique with polypropylene suture. The data of desired variables can be accessed easily just by few clicks. Conclusions: This mobile app is reliable, fast, cost effective, and generates a credible and valid data along with the basic statistical analysis.